Sexuality behind bars in the female central penitentiary of Santiago, Chile: Unlocking the gendered binary. Issue 1 (January 2017) - Castro Madariaga, Francisca Alejandra; Gómez Garcés, Belén Estefanía; Carrasco Parra, Alicia; Foster, Jennifer
Abstract : We explore what it means to promote healthy sexuality for incarcerated women. We report upon the experiences of ten inmates in the Female Central Penitentiary of Santiago, Chile, regarding their sexuality within prison. We used a qualitative, descriptive research approach. Individual and semistructured interviews were conducted with women from different sections of the prison over a 2‐month period. Participants highlighted the site for conjugal visits, the Venusterio, as a place of privacy and sexual expression between couples from outside prison. Motivated by loneliness, need of protection, and desire for affection, participants enacted alternate gender and sexual identities and sexual orientation. Some previously heterosexual women became 'machos', women taking on dominant masculine identities. Women found a paradoxical freedom to express a malleable and fluid sexual identity, an identity that might not go outside the prison. Informed by Judith Butler's idea of performativity, we argue that women could enact both different gender and sexual identities in search of satisfying their affective and erotic desires while under the duress of incarceration. The findings suggest a need for a more fluid understanding of gender and sexuality, especially for those midwives and nurses who strive to promote sexual health, not only reproductive health.